Manfaat Puja Bakti dalam Meningkatkan Keyakinan kepada Buddha Dharma (Penelitian Tindakan Kelas Peserta Didik Kelas X) di SMKS Kasih Maitreya Selatpanjang - Mario Anita; Sonika Sonika (Jurnal Maitreyawira, 2024)
Finding out how Puja Bakti is used to increase belief in Buddha Dharma through Buddhist education classes in class X at SMKS Kasih Maitreya-Selatpanjang is the aim of this action research project. The findings of the study using techniques for planning, carrying out, observing, and reflecting. The results of the learning and comprehension of devotional service demonstrate that it has been well implemented. The average student understanding increased from 77 in the pre-cycle to 83 in the first cycle and then to 88 in the second cycle until all students had completed (> 75 KKM) receiving Buddhist Education lessons. In percentage terms, the understanding increased by 9% in the first cycle and 19% in the second cycle to 100%. This demonstrates that pupils have a successful comprehension of and application of Buddhist education and Puja Bakti. Teachers of Buddhist education participate more actively in the monastery's Puja Bakti implementation.